Borges and Tango Metaphysics in Fervor de Buenos Aires - Orduz Rodríguez, Frank Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2020)
Jorge Luis Borges found an expressive and transcendental force in the existential depth of tango that is crystallized in his work. This paper proposes the examination of the relationship between time and space that, from tango, composed in Fervor de Buenos Aires, by Borges. From Borges’ own approaches to time, metaphysical foundations, approaches to tango, and Borgesian work, this paper examines the recovery of lost space through the poetic revaluation of time, very tango-style, in the poems of Fervor de Buenos Aires. In Fervor de Buenos Aires, the inner movement that the lyric subject, like the subject of tango, makes to rescue the identity of the instant is poetize. Consequently, Borges displays a metaphysical understanding of the emblematic places of tango, the reason why his conception of time is not ubiquitous and the subject of his poems, similar to the tangos, is turned to the encounter with timeless ideas of lost spaces.